In Situ Control of Reactive Mesogens Alignment During 3D Printing by Two‐Photon Lithography - Tiziana Ritacco; Alfredo Mazzulla; Michele Giocondo; Gabriella Cipparrone; Pasquale Pagliusi (Advanced Science)
Abstract Photopolymerizable liquid crystals, also known as reactive mesogens, are leading candidates for additive manufacturing of smart microdevices via two‐photon lithography (TPL). While substantial advancements are made toward innovative applications, precise control of molecular alignment during fabrication, essential for tailoring complex optical and mechanical responses, remains a significant challenge. Current solutions require elaborate multi‐step procedures or customized setups to achieve 2D or 3D alignment patterns. Herein, the deterministic effect of TPL on the orientation of mesogenic moieties is reported, under optimized printing conditions. Specifically, a single‐step simple method is developed for aligning the nematic director in situ, with sub‐diffraction‐limited resolution, during 3D printing. Based on the conventional TPL workflow, the “director‐tuning mode” (DiTuM) relies on the anisotropic photopolymerization reaction occurring along the print path at low laser scan speeds (≈0.1mm s−1). A TPL‐induced “easy axis” arises for the mesogenic moieties, programmable in direction and strength, and competes with the initial alignment to create potentially convolute 3D director fields. The method holds considerable promise for 3D/4D printing, enabling advanced functionalities, and offers a robust platform for anti‐counterfeiting applications, leveraging the unique optical signatures generated by complex microstructures.